Please note that:
1/(k(k+1)) = 1/k - 1/(k+1).
Thus, the sum from 1 to 4 would be:
1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + 1/4 - 1/5.
Do you see what's happening here? All the middle terms cancel each other out, leaving only the terms on the end. Therefore, [k=1, n]∑1/(k(k+1)) = 1 - 1/(n+1). This may be proven formally by induction as follows:
First, note that this holds true for n=1, since [k=1, n]∑1/(k(k+1)) = 1/2 = 1-1/2, which is what we get by plugging n into the formula. Now suppose it holds for some n -- then [k=1, n+1]∑1/(k(k+1)) = [k=1, n]∑1/(k(k+1)) + 1/((n+1)(n+2)) = 1 - 1/(n+1) + 1/((n+1)(n+2)) = 1 - 1/(n+1) + 1/(n+1) - 1/(n+2) = 1 - 1/(n+2), which is what we would get by substituting n+1 into the formula. Therefore, if it holds for some n, it must also hold for n+1, and since it holds for 1, then by induction, it holds for all natural numbers. Q.E.D.
Edit: Well, looks like I've been beaten to the punch. Of course, this also agrees with the formula you found, since n²/(n(n+1)) = n/(n+1) = 1 - 1/(n+1).
2007-03-08 01:42:03
·
answer #1
·
answered by Pascal 7
·
1⤊
0⤋
Your suggested answer appears to be correct. You prove it using induction.
1. Prove that it works for n=1. This is easy
2. Prove that IF it works for n = k, then it also works for n=k+1.
So Sum(1/(i(i+1))) = k²/k(k+1)
Add term for k+1:
S(k+1 terms) = k²/(k(k+1)) + 1/((k+1)(k+2)
See can you work this round to be equal to (k+1)²/((k+1)(k+2))
If so, the proposition is proved.
2007-03-08 01:39:47
·
answer #2
·
answered by Gnomon 6
·
1⤊
0⤋
The result is easily obtained by splitting the expression into partial fractions. This gives 1/(i+1) - 1/i.
For i from 1 to n, this sums to 1/(n+1) -1 = n/(n+1).
Your answer is correct. You can cancel an n from top and bottom.
2007-03-08 01:38:49
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
1/(i(i+1)) = 1/i - 1/(i+1).
It follows:
sum(from 1 to n)[1/(i(i+1))]
= 1 - 1/2 + 1/2 - 1/3 + 1/3 - 1/4 + .....+1/(n-1) - 1/n + 1/n - 1/(n+1)
= 1 - 1/(n+1)
= n/(n+1).
So, you are correct.
2007-03-08 01:37:52
·
answer #4
·
answered by fernando_007 6
·
1⤊
0⤋
1/i(i+1) = 1/i - 1/(i+1)
when we add from i =1 to n they cancell out and we are left with
1 - 1/(n+1) or n/(n+1)
your solution reduces to n/(n+1) when we cancell n so you are right
step
1/1 - 1/2 + 1/2 - 1/3 ....- 1/n + 1/n - 1/(n+1) = 1- 1/(n+1)
2007-03-08 01:37:52
·
answer #5
·
answered by Mein Hoon Na 7
·
1⤊
0⤋
You are correct, though it reduces to n/(n+1).
Can do a proof by induction. Show for n=1 or two...assume it works for n and then show it will work for n+1...gotta go...maybe I'll show later...
2007-03-08 01:34:01
·
answer #6
·
answered by runningman022003 7
·
1⤊
0⤋